Invisibility, stigma and workplace support: Experiences of individuals with chronic disorders - Armand Bam (SA Journal of Human Resource Management)
Orientation: Individuals with chronic disorders such as systemic lupus erythematosus (SLE) face challenges in disclosing their condition at work due to symptom invisibility and stigma. Managers play a crucial role in managing employees as stakeholders and shaping workplace culture and inclusivity.